Activation of titanium-vanadium alloy for hydrogen storage by introduction of nanograins and edge dislocations using high-pressure torsion. (8th June 2016) - Edalati, Kaveh; Shao, Huaiyu; Emami, Hoda; Iwaoka, Hideaki; Akiba, Etsuo; Horita, Zenji
Abstract: Ti–V alloys thermodynamically absorb hydrogen at room temperature, but hydrogenation does not occur practically without a sophisticated activation process. In this study, a nanograined TiV alloy with the supersaturated bcc structure and an ultrahigh density of edge dislocations (>10 16  m −2 ) was mechanically synthesized from Ti and V powders using the high-pressure torsion (HPT) method. The presence of large fractions of grain boundaries and dislocations, as effective pathways for hydrogen diffusion, activated TiV and it absorbed ∼4 wt.% of hydrogen at room temperature after an incubation period. The kinetic measurements suggested that the hydrogen absorption in the incubation period is controlled by the slow rate of hydrogen dissociation, while the hydrogenation rate in the latter stage is controlled by diffusion of hydrogen atoms. Highlights: A TiV alloy is synthesized from Ti and V powders by high-pressure torsion method. The HPT-processed TiV is active and fully absorbs hydrogen at room temperature. The activation is due to large fractions of grain boundaries and edge dislocations.